PENGARUH FIRM IMAGE DAN AFFECTIVE LOYALTY TERHADAP WORD OF MOUTH PADA KONSUMEN PRODUK KOSMETIK WARDAH DI YOGYAKARTA - erika ayu cahyapuspita (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to examine the effect of firm imageand affective loyalty on WOM. This research was conducted in 162 respondents in Yogyakarta with respondents who used anad bought wardah cosmetic products once or more. The resultsof this study indicate: 1)firm image has a positive effect on WOM, 2) affective loyalty has a positive effect on WOM.